1990
DOI: 10.1002/prop.2190380502
|View full text |Cite
|
Sign up to set email alerts
|

Can QCD Be a Perturbation Theory of Hadrons?

Abstract: We have found that the S‐matrix for atoms and hadrons depends on a gauge as the elementary particles are off mass‐shell in the bound states. The S‐matrix for bound states one should to construct by the projection of the Belinfante energy‐momentum tensor on the Gauss equation solution for the time component with the time‐axis chosen as the eigenvector of the bound state total momentum operator. We have shown that this QCD Hamiltonian determined in infrared region by the rising potential ansatz, besides the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Below we shall use propagator in momentum space, G z ( q ) , is conveniently parametrized through the functions E ( k , ) and p( k, ) (de-~( r ) = ( f ) v o r 2 , Vo=const . Pervushin and collaborators [2][3][4][5]131 have shown that with kernels of the form (61, this BSE is also manifestly 1 Lorentz covariant. E ( k ) = r n s i n p ( k ) + k cosp(k)-fp'(k)-=cos2p(k) , To solve the BSE, we should decompose $Lb) over the n Dirac y matrices [4,5,9,13].…”
Section: Schwinger-dyson and Bethe-salpeter Equations For The Harmonimentioning
confidence: 98%
See 3 more Smart Citations
“…Below we shall use propagator in momentum space, G z ( q ) , is conveniently parametrized through the functions E ( k , ) and p( k, ) (de-~( r ) = ( f ) v o r 2 , Vo=const . Pervushin and collaborators [2][3][4][5]131 have shown that with kernels of the form (61, this BSE is also manifestly 1 Lorentz covariant. E ( k ) = r n s i n p ( k ) + k cosp(k)-fp'(k)-=cos2p(k) , To solve the BSE, we should decompose $Lb) over the n Dirac y matrices [4,5,9,13].…”
Section: Schwinger-dyson and Bethe-salpeter Equations For The Harmonimentioning
confidence: 98%
“…Pervushin and collaborators [2][3][4][5]131 have shown that with kernels of the form (61, this BSE is also manifestly 1 Lorentz covariant. E ( k ) = r n s i n p ( k ) + k cosp(k)-fp'(k)-=cos2p(k) , To solve the BSE, we should decompose $Lb) over the n Dirac y matrices [4,5,9,13]. Since in this work we are in-(1 1) terested only in the pseudoscalar mesons r , r 1 , K , K ' , we simply have Our solutions for p ( k ) , E T ( k ) , L l ( k ) , and L 2 ( k ) (obtained by the Adams-Bashfort method) agree with the ones in Ref.…”
Section: Schwinger-dyson and Bethe-salpeter Equations For The Harmonimentioning
confidence: 98%
See 2 more Smart Citations
“…The rising potentials of the instantaneous interactions of colour currents [39,40,41] also lead to a spontaneous breakdown of the chiral invariance for quarks.…”
Section: Topological Degeneracy Of Bps Monopolementioning
confidence: 99%